2022
DOI: 10.3389/fmed.2022.986825
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol attenuated diabetic nephropathy by reducing apoptosis and promoting autophagy through AMPK/mTOR pathways

Abstract: IntroductionRenal podocyte injury, apoptosis and autophagy are involved in the occurrence and development of diabetic nephropathy (DN). Kaempferol (KPF) has the promotion of autophagy and inhibition of apoptosis properties in the development of miscellaneous diseases, but these functions in DN have not yet been elucidated.MethodsWe used db/db mice to evaluate the protective role of KPF on DN. The anti-DN effect of KPF was evaluated by urine albumin-to-creatinine ratio and pathological changes of kidney tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…[28][29][30][31] Kaempferol has been demonstrate to reduce mesangial matrix expansion, glomerular basement membrane and podocyte loss by inhibiting apoptosis and promoting autophagy through AMPK/mTOR pathways, thereby protecting the kidney. [32] It was found that Astragalus membranaceus could inhibit renal fibrosis and inflammation, as well as reduce blood creatinine and cystatin, thus playing a protective role in the kidney. [33,34] Moreover, studies have shown that naringenin may inhibit the expression of inflammatory cells, attenuate oxidative stress and the accumulation of extracellular matrix in the glomerulus, exhibiting renal protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Kaempferol has been demonstrate to reduce mesangial matrix expansion, glomerular basement membrane and podocyte loss by inhibiting apoptosis and promoting autophagy through AMPK/mTOR pathways, thereby protecting the kidney. [32] It was found that Astragalus membranaceus could inhibit renal fibrosis and inflammation, as well as reduce blood creatinine and cystatin, thus playing a protective role in the kidney. [33,34] Moreover, studies have shown that naringenin may inhibit the expression of inflammatory cells, attenuate oxidative stress and the accumulation of extracellular matrix in the glomerulus, exhibiting renal protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…178,179 Additionally, kaempferol exhibits a capacity to alleviate renal histological and functional damage in db/db mice. 145 Kaempferol treatment leads to a decrease in the urine albumin-to-creatinine ratio and reduces the accumulation of extracellular matrix. The stimulation of autophagy through the activation of AMPK and inhibition of mTOR is suggested to be a contributor for these beneficial effects of kaempferol.…”
Section: Kaempferolmentioning
confidence: 99%
“…The antidiabetic activity of kaempferol has been indicated in HFD‐induced diabetic mice 178,179 . Additionally, kaempferol exhibits a capacity to alleviate renal histological and functional damage in db / db mice 145 . Kaempferol treatment leads to a decrease in the urine albumin‐to‐creatinine ratio and reduces the accumulation of extracellular matrix.…”
Section: Natural Products That Promote Autophagy and Improve T2dmmentioning
confidence: 99%
“…It alleviates mesangial matrix expansion and podocyte loss or fusion in DKD. It slows DKD progression by upregulating podocyte autophagy via the AMPK/mTOR pathway, evidenced by increased LC3II, Beclin-1, p-AMPK, Bcl-2, Atg7, and Atg5, and decreased p-mTOR, Bax, caspase-3, and p62 expression ( Sheng et al, 2022 ). Mangiferin and phenolics from Physalis peruviana fruits have both been shown to exert a protective effect on the kidney by enhancing autophagy through the AMPK/mTOR pathway ( Wang X. et al, 2018 ; Ezzat et al, 2021 ).…”
Section: Natural Products For Regulating Diabetic Microvascular Compl...mentioning
confidence: 99%